Implementation of the Tahfidzul Quran Program to Build Patient Character in Elementary School Students - Reza Faqih; Ida Rindaningsih (Universitas Muhammadiyah Sidoarjo, 2023)
This thesis writing discusses the tahfidz qur'an program applied in SD Muhammadiyah 2 socah which bears the values of patience. The problem in this case focuses on the values of patience as a result of the Qur'anic tahfidz program. This type of research is qualitative phenomenology, in this case the author found a unique thing to discuss because the values of patience can arise from the qur'anic tahfidz program. Data collection techniques use observation, interview and sokumentation. The data analysis techniques used are data validation, data reduction, presenting findings and validation of findings. The results of this study found that in the implementation of the qur'an tahfidz program formed a patient character in muhammadiyah 2 socah elementary school students, namely: the stage of planning, implementation, and assessment related to the qur'an tahfidz program with the values of patience. The advantages and disadvantages of the methods used in teaching, the advantages that many bring patience to learners than before, the lack of teachers still has difficulty understanding students who are really lancer and fluent in memorizing the Qur'an.